2018
DOI: 10.3389/fmars.2018.00460
|View full text |Cite
|
Sign up to set email alerts
|

A Multi Criteria Assessment Method for Identifying Vulnerable Marine Ecosystems in the North-East Atlantic

Abstract: In international fisheries management, scientific advice on the presence of "vulnerable marine ecosystems" (VMEs) per United Nations resolutions, has generally used qualitative assessments based on expert judgment of the occurrence of indicator taxa such as cold-water corals and sponges. Use of expert judgment alone can be criticized for inconsistency and sometimes a lack of transparency; therefore, development of robust and repeatable numeric methods to detect the presence of VMEs would be advantageous. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 37 publications
0
63
0
Order By: Relevance
“…As well as considering spatio-temporal patterns at the basinscale, we examine temporal changes at fourteen case study sites (Figure 1 and Table 1). These sites were chosen to represent a variety of potentially vulnerable deep-sea ecosystems across the northern North Atlantic region as indicated by VME indicator records (Morato et al, 2018). The sites also include a number of existing, or proposed, Marine Protected Areas (MPAs), Ecologically or Biologically Significant Areas (EBSAs), and VME closures (Johnson et al, 2018).…”
Section: Ecosystem Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as considering spatio-temporal patterns at the basinscale, we examine temporal changes at fourteen case study sites (Figure 1 and Table 1). These sites were chosen to represent a variety of potentially vulnerable deep-sea ecosystems across the northern North Atlantic region as indicated by VME indicator records (Morato et al, 2018). The sites also include a number of existing, or proposed, Marine Protected Areas (MPAs), Ecologically or Biologically Significant Areas (EBSAs), and VME closures (Johnson et al, 2018).…”
Section: Ecosystem Case Studiesmentioning
confidence: 99%
“…four sites have maximum depths below 3500 m ( Table 1), there is no site that truly represents the abyssal plains of the North Atlantic south of 50 • N. This reflects the current absence of VME indicator records in these areas (Morato et al, 2018). Time-series were constructed for each case study site.…”
Section: Ecosystem Case Studiesmentioning
confidence: 99%
“…Confidence in the resulting score is then assigned based on four further criteria: survey method (e.g., trawl vs. ROV), number of surveys to the area, the time range of the surveys undertaken, and the time since the last survey. Detailed results of this application are presented in Morato et al (2018).…”
Section: Spatial Management and Protection Measures Fishery Closuresmentioning
confidence: 99%
“…The criteria have mostly been applied to "indicator" species, or higher-level taxa, resulting in methods that primarily use the presence of indicator taxa to identify VME locations. These methods have become increasingly quantitative, progressing from relatively simple threshold approaches (e.g., Auster et al, 2011) to multi-criteria mapping that combines information on the vulnerability traits and abundances of target taxa with estimates of the confidence in data quality (Morato et al, 2018). Quantitative measures of indicator taxa density and spatial extent of associated habitat are viewed as the preferred technique to identify VMEs, but in the deep sea this is rarely possible using data that are independent from fisheries bycatch information (Ardron et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The best performing models may vary according to the structure of the underlying community and how the data are collected, substantiating the approach of using multiple models and assessing the consistency between them (Norberg et al, 2019). Even where multi-criteria assessments (Morato et al, 2018) take account of abundance in point collections of fauna (e.g., fishery bycatch), there is uncertainty about how well the collections represent faunal density on the seabed because of gear selectivity and differences in the catchability of taxa. In situ photographic image data have the potential to provide abundance data on deep-sea VME taxa when the field-of-view is quantified (Althaus et al, 2009;Clark et al, 2019), and have shown that physical (sled) collections in the deep-sea are prone to underestimate faunal density -possibly by a considerable degree (Williams et al, 2015).…”
Section: Introductionmentioning
confidence: 99%